A Clinical Association of Dry Socket and Postoperative Pain with Typhoid fever as Risk Factor - Faraed D Salman; Mahmoud YM Taha (University of Mosul, College of Dentistry, 2011)
Aims: To identify the clinical picture and the association between dry socket and severe postoperative development with one of the systemic risk factors (typhoid fever). Materials and Methods: Twenty adult (both sexes) patients attended dental clinic searching for different dental treatments were studied. The clinical picture of 6 months period study was evaluated by completing two case sheet forms. They were diagnosed having dry sockets and severe postoperative pain. Blood samples were taken for bacte-riological, serological and hematological study to diagnose typhoid fever. These tests included WAT, WFT, WBCs and blood culture. Results: Significant correlation existed between postoperative pain and typhoid fever examined by BC and the highest percentage was with dry socket (61.5%) followed by WFT (57.1%(, WAT (44.4%) using two tests for diagnosis showed that WFT and BC gave 97.9% positive for dry socket and Kappa test was 88%, while WAT and WBCs or WFT and WAT gave the least non significant correlation. Conclusion: There was a strong correlation between dry socket and typhoid fever and the most sensitive tests for diagnosis was BC followed by WFT, WBCs and WAT.